Expression of the Gene Encoding the Brucella abortus BAB1-0278 Antigen in Probiotic Lactococcus lactis Bacteria - donya kazemi; abbas doosti; mostafa Shakhsi niaee (مجله علمی دانشگاه علوم پزشکی کردستان)
Background and Aim: The BAB1-0278 has an essential role in abortus infection. This antigen encodes a protein called GcrA, which plays an essential role in the transcription of target genes in the cell cycle. Thus, BAB1-0278 has unique potential in therapeutic strategies against B. abortus. The purpose of this research is to produce engineered Lactococcus lactis bacteria expressing the BAB1-0278 protein of B. abortus. Materials and Methods: The gene construction design contains a signal peptide sequence in the nisin-based expression vector (pN3z8148-Usp45-BAB1-0278) and is synthesized by GENEray. The recombinant plasmid transformed into Escherichia coli bacteria. The recombinant plasmid was extracted from transformed bacteria. L. lactis transformed by electroporation both with the recombinant plasmid containing the target gene pNZ8148-Usp45-BAB1-0278 and the plasmid without the target gene. BAB1-0278 expression was confirmed by reverse polymerase chain reaction (RT-PCR) and sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and western blot techniques. Results: B. abortus BAB1-0278 was expressed in L. lactis and confirmed by RT-PCR. SDS-PAGE analysis of proteins isolated from L. lactis transformed with recombinant plasmid, compared to untransformed L. lactis, showed a protein with a molecular weight of 13 kDa. Conclusion: The results of PCR, restricted enzyme digestion, and sequencing by GENEray revealed that BAB1-0278 was cloned correctly in pNZ8148-Usp45. SDS-PAGE and Western blot were used to analyze BAB1-0278 protein expression. Transformed L. lactis can be a crucial step for oral vaccine research against B. abortus.